Marriage and fidelity in “The unfaithful married” by Federico García Lorca - Rodríguez Chávez, Iván (2018)
Lyric poem that, within the topic of love, develops the theme of marriage in its moral and legal attribute of fidelity, highlighting that the real practice of this value depends not only on a woman as one of the members of a couple, but of a third party who, knowing he does, intentionally gets involved with her to break that marital bond. The abstention of the third party contributes to the real and formal validity of fidelity.